REGISTER USED BY INDONESIAN CASTERS IN ONLINE GAME (MOBILE LEGENDS: BANG-BANG) - Agus Darma Yoga Pratama (Universitas Warmadewa, 2022)
The register is a part of language variations that is appeared in a different groups of society. A different way of speaking can carry different social meanings. A group of society may have a different form of language that surely has a different meaning. This research aims to find out the form of the registers used by Indonesian casters in an online game (Mobile Legends: Bang-Bang) and to describe the function of registers that are used by Indonesian casters in an online game (Mobile Legends: Bang-Bang). Based on the analysis that has been carried out, there are 43 register data used by Indonesian casters in the final mobile legends (Indonesia vs the Philippines). The classification of register forms is divided into lingual units of words, and lingual units of phrases. Based on the lingual unit of a single word includes 19 data, and the lingual unit of the phrase consists of 24 data. Then, there are three register functions used by Indonesian casters in mobile legends, namely: a) usage of registers to make communication more effective; b) the use of registers intends to attract the interest of language users in communicating; c) the existence of a register can distinguish one language from another. It is suggested to the interested parties who want to conduct another research in the same field to research other types of online games such as jargon, code mixing, code switching, slang, language variations, and various other interesting topics in the field of sociolinguistics.